Evaluation of Overseeding and Colorants on ‘Chisholm’ Zoysiagrass during Winter Dormancy - R. Braun; J. Fry; M. Kennelly; D. Bremer; J. Griffin (Kansas Agricultural Experiment Station Research Reports, 2015)
Annual ryegrass overseeding into lawn-height zoysiagrass provided acceptable turf color for only four weeks. The colorant Green Lawnger provided a darker green and considerably longer duration of acceptable color as compared to the colorant Match Play (bermudagrass), which was lighter green on zoysiagrass. A single colorant application resulted in acceptable turf color for 7 to 24 weeks; a sequential midwinter application provided acceptable color until spring greenup.
Keywords: turfgrass; & #x27; Chisholm& #x27; zoysiagrass; overseeding; colorants; Green Lawnger; Match Play bermudagrass